К истории сочетаний глаголов с поствербами в английском языке - Клиюнайте, Ина (Kalbotyra, 1995)
The aim of this article is to survey the history of development of the English units “verb + postverb” of the type walk in, think out, put up during different periods of the development of language and to define them as functionally single units – analytical words with a second element as a derivative morpheme.